Treatment of Heart Failure in Patients with Ischemic Cardiomyopathy Using Cell Therapy - Usenko, O.; Gabriyelyan, A.; Smorzhevskyi, V.; Kudlai, I.; Marchenko, O. (Transplantation and artificial organs, 2025)
Objective. Investigate the effect of cord blood stem cells on the course of heart failure in patients with ischemic cardiomyopathy. Materials and methods. The study included 113 patients with ischemic cardiomyopathy comparable in age, sex, and basic clinical parameters. Patients were divided into four groups depending on the treatment methods: coronary artery bypass grafting (CABG) – 35 patients (33%), coronary stenting (CS) – 38 patients (31%), coronary revascularization and stem cells transplantation (CR+SCT) – 20 patients (18%), medical treatment (MT) – 20 patients (18%). The observation period was 48 months. Results. During the first year of the study, the mean LVEF increased by 1.7 times for the CR+SCT group (from 24.8% before treatment to 37.2% after 1 year and 31.9% after 4 years). BNP results changed from a baseline of 998 pg/ml after 12 months to 377 pg/ml. After further stabilization over the next three years, BNP results stabilized at 382 pg/ml. The quality of life of patients improved (confirmed by the results of the Minnesota questionnaire). At the beginning of the study, the total score for patients was 56.8, and after 48 months, it decreased to 46.1 for the CR 46.1, compared with other groups (CABG – 55.8; CS – 55.2; MT – 62.8). Conclusion. The use of stem cell transplantation in combination with coronary revascularization in patients with ischemic cardiomyopathy contributes to the improvement of the clinical course of the disease, an increase in LVEF, a decrease in the severity of heart failure symptoms, and an improvement in the quality of life of patients. The results obtained confirm the feasibility and prospects of using cell technologies in this category of patients.